Socket shield: An esthetic success? - Farhan Durrani; Himani Painuly; Akanksha Shukla; Samidha Pandey; Rakhshinda Nahid (Wolters Kluwer Medknow Publications, 2020)
Dental implants require adequate bone, three dimensionally, for successful osseointegration. The extraction socket changes in the dimension had been described in several studies. Implant in extraction socket cannot prevent resorption of the surrounding tissues. The bony alterations make oral esthetic implant reconstruction difficult without hard- and soft-tissue augmentation. Placement of bone substitute material and immediate implant were not able to completely establish an esthetic outcome. A novel technique of retaining the buccal aspect of the tooth root during implant placement has shown preservation of esthetics. Hard and soft tissues were preserved in their original form around the replaced tooth. The retained root on the buccal aspect of an oral implant is observed to have formed cementum and to some aspects of osseointegration with the surrounding tissues. It is called socket-shield technique and if completed meticulously can be an alternative for regenerative materials and soft-tissue grafting. In our report, we completed 14 cases of the said technique with 5-year follow-up. The results looked promising as none of the cases required guided bone regeneration procedures. This may become the future noninvasive method for the preservation of hard and soft tissues around an oral implant in esthetic areas.